2021
DOI: 10.3390/tropicalmed6040212
|View full text |Cite
|
Sign up to set email alerts
|

Myocarditis in a Pediatric Patient with Campylobacter Enteritis: A Case Report and Literature Review

Abstract: Myocarditis represents a potential complication of various infectious and noninfectious agents and a common diagnostic challenge for clinicians. Data regarding Campylobacter-associated myocarditis are limited. Here, a case of a 13-year-old female with Campylobacter jejuni gastroenteritis complicated by myocarditis is presented, followed by a literature review in order to retrieve information about Campylobacter-associated carditis in the pediatric population. A search on MEDLINE/PubMed yielded 7relevant cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Cardiac symptoms are not an uncommon manifestation in Chikungunya infection and may have high mortality rates, as evidenced by an extensive literature review by Traverse et al [ 13 ]. Finally, two studies reported interesting cases and reviewed the literature on severe odontogenic infections during pregnancy [ 14 ] and Campylobacter myocarditis [ 15 ].…”
Section: Epidemiologically Important Diseasesmentioning
confidence: 99%
“…Cardiac symptoms are not an uncommon manifestation in Chikungunya infection and may have high mortality rates, as evidenced by an extensive literature review by Traverse et al [ 13 ]. Finally, two studies reported interesting cases and reviewed the literature on severe odontogenic infections during pregnancy [ 14 ] and Campylobacter myocarditis [ 15 ].…”
Section: Epidemiologically Important Diseasesmentioning
confidence: 99%
“…However, cases of invasive disease such as bacteraemia [ 2 ] have also been attributed to C. jejuni infection. In addition, C. jejuni gastroenteritis (campylobacteriosis) has been associated with myocarditis [ 3 ], as well as with many long-term sequalae, including dysbiosis, irritable bowel syndrome (IBS), and Guillain-Barré syndrome (GBS). C. jejuni gastroenteritis is a zoonotic disease: C. jejuni is transmitted to humans from animals, primarily chickens, where C. jejuni is part of normal intestinal microbiota, but can also be transmitted from cattle, pigs, sheep and, as the more recent evidence suggests, domestic cats and dogs [ 4 ].…”
Section: Introductionmentioning
confidence: 99%